1997
DOI: 10.1111/j.1365-2249.1997.tb08336.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 sensitizes human pre-B cells but not pro-B cells to Fas/APO-1 (CD95)-mediated apoptosis

Abstract: SUMMARYHomeostasis of human B cell development is maintained by a complex network of cytoplasmic and surface expressed molecules. Abnormalities in this process may result in the expansion of malignant B cell precursors in B lineage acute lymphoblastic leukaemia (ALL). ALL cells share surface antigens with normal early precursor B cells. We have studied here the role of Fas/APO-1 (CD95) antigen on leukaemic precursor B cell line growth and survival, and the modulation of its effects by signals involved in norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The reasons for the latter are unclear but IL-7 and IL-3 have been reported to induce differentiation and apoptosis in a subpopulation of ALL cells. 35,40 Synergistic interactions between CXCL12 and Flt-3 ligand, granulocyte-macrophage colony-stimulating factor, stem cell factor and thrombopoietin have been observed in normal and leukemic myeloid progenitors cultured in the absence of stroma, resulting in enhanced survival, chemotaxis and proliferation. 21,41 In these studies CXCL12-enhanced responses to cytokines were associated with augmented signaling through ERK/MEK and PI-3K/AKT pathways, although the causative role of this was not always confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the latter are unclear but IL-7 and IL-3 have been reported to induce differentiation and apoptosis in a subpopulation of ALL cells. 35,40 Synergistic interactions between CXCL12 and Flt-3 ligand, granulocyte-macrophage colony-stimulating factor, stem cell factor and thrombopoietin have been observed in normal and leukemic myeloid progenitors cultured in the absence of stroma, resulting in enhanced survival, chemotaxis and proliferation. 21,41 In these studies CXCL12-enhanced responses to cytokines were associated with augmented signaling through ERK/MEK and PI-3K/AKT pathways, although the causative role of this was not always confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Cells expressing equivalent levels of cell-surface Fas may differ in susceptibility to Fas-mediated death [10], and this susceptibility may be altered within a cell type, e.g., by stimulation of cytokine receptors [34][35][36]. We therefore examined the induction of apoptosis by Fas ligation in inflammatory compared with peripheral blood neutrophils, and the suppression of this death by co-incubation with a neutrophil survival factor.…”
Section: Signaling Via the Fas Death Receptor Pathway Does Not Regulamentioning
confidence: 99%
“…Fas receptor depend on the state of cell activation and, in particular, on the costimuli provided to the cells on which Fas receptor has been engaged [10][11][12][13][14]. Fas is involved in the homeostasis of the immune system, mainly by inducing cell death of activated B and T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that programmed cell death of human pre-B cell lines can be triggered by crosslinking of membrane Fas protein and that IL-7 enhances Fas-induced apoptosis of pre-B but not pro-B cell lines [14]. In addition, pre-B cell receptor (pre-BCR) ligation significantly potentiates IL-7 effects on Fas-triggered pre-B cell death.…”
Section: Introductionmentioning
confidence: 99%